Hydrophilic α-Aryl-α-Diazoamides for Protein Esterification - Okon, Aniekan; Morgunov, Anton; Yang, Jinyi; Petri, Yana D.; Kilgore, Henry R.; Li, Yanfeng; Strieter, Eric R.; Raines, Ronald T. (Synlett, 2025)
Bioreversible protein esterification is a simple, customizable, and traceless strategy for the exogenous delivery of proteins into mammalian cells. Enabling this protein delivery strategy are α-aryl-α-diazoamides bearing a tolyl moiety. The aqueous solubility of the ensuing esterified protein is, however, often compromised, which can result in the loss of soluble esterified protein for downstream applications. Here, we undertook a structure–activity relationship campaign to generate hydrophilic diazoamides for use as protein esterification and cellular delivery agents. We find that the careful adjustment of the hydrogen-bond basicity of α-aryl-α-diazoamides is sufficient to engender soluble esterified proteins, as high hydrogen-bond basicity correlates with high aqueous solubility. Importantly, enhancing aqueous solubility of diazoamides should proceed pari passu with preserving their lipophilicity and reactivity towards esterification of carboxylic acids, as the best-performing diazoamide from our study contains an N-acetyl piperazine while retaining the tolyl moiety. Our efforts can inspire new generations of esterified proteins with better solubility.
Keywords: cell; delivery; diazo compounds; esterification; hydrophilicity; hydrophobicity; proteins; solubility